Molecular interactions of plant-derived inhibitors from Euphorbia hirta against binding sites of HPV E6 and E7 oncoproteins - An in-silico analysis - J, Jothi; K, Balagurusamy; S, Suresh; Gladys R, Jeeva (International Journal of Ayurvedic Medicine, 2024)
Although no cure for Human Papilloma virus (HPV) exists at the moment, effective vaccines are present that can prevent the most harmful strains of the virus from infecting people. While potential cures like therapeutic vaccines, immunotherapy, and gene therapy are still in the early stages of development and may take years to become widely available, we focussed on using traditional Siddha-based medicines (phytochemicals of Euphorbia hirta L.) as a prospect through in-silico docking studies. Twelve phytochemicals from Euphorbia hirta L. were selected to investigate the antiviral properties against HPV. These ligand structures were obtained from PubChem database, prepared for docking with two major HPV targets i.e., E6 and E7 oncoproteins obtained from PDB, using AutoDock tools. The analysis revealed the potential of lobeline and euphol ligands effectively binding to the active sites of E6 and E7 proteins respectively. Using the ADMET lab 2.0 server, the ligands were evaluated for their commercial drug potential by considering their absorption, distribution, metabolism, excretion, and toxicity properties.